Individual Differences in Signal Perception for Takeover Request in Autonomous Driving - Okkeun Lee; Hyunmin Kang (Applied Sciences, 2023)
In the context of partial autonomy, where autonomous vehicles and humans share control of the vehicle, bringing out-of-the-loop drivers back into the loop is a significant challenge. While warning signal design guidelines are commonly used to provide alerts, few studies have examined each signal in depth with an emphasis on the autonomous environment. This study aims to fill this gap by investigating visual, auditory, and tactile stimuli and modifying their sub-attributes to explore variations related to age, gender, and other individual backgrounds. For this objective, the research examined the correlations between age, gender, and individual backgrounds with reaction times to TOR signals, investigating the effects of sub-attribute variations on participants’ responses and exploring the subjective evaluations of the signals. A driving simulator was utilized to create a realistic driving environment and measure participants’ reaction times in takeover request situations. Analysis of the data revealed correlations between age and reaction times for auditory and tactile signals, with interaction effects observed between age and sub-attribute intensity. Additionally, participants exhibited varying reaction time patterns in response to different sub-attribute intensities. By evaluating individual differences in perception based on modality characteristics, often overlooked in prior research, this study serves as a foundational contribution to future research in the field.